Isolation and Characterization of a Novel Ribosome-Inactivating Protein from Root Cultures of Pokeweed and Its Mechanism of Secretion from Roots - Park, Sang-Wook (American Society of Plant Physiologists, 2002)
Ribosome-inactivating proteins are N-glycosidases that remove a specific adenine from the sarcin/ricin loop of the large rRNA, thus arresting protein synthesis at the translocation step. In the present study, a novel type I ribosome-inactivating protein, termed PAP-H, was purified from Agrobacterium rhizogenes-transformed hairy roots of pokeweed (Phytolacca americana). The protein was purified by anion- and cation-exchange chromatography. PAP-H has a molecular mass of 29.5 kD as detected by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and its isoelectric point was determined to be 7.8. Yeast (Saccharomyces cerevisiae) ribosomes incubated with PAP-H released the 360-nucleotide diagnostic fragment from the 26S rRNA upon aniline treatment, an indication of its ribosome-inactivating activity. Using immunofluorescence microscopy, PAP-H was found to be located in the cell walls of hairy roots and root border cells. PAP-H was determined to be constitutively secreted as part of the root exudates, with its secretion enhanced by a mechanism mediated by ethylene induction. Purified PAP-H did not show in vitro antifungal activity against soil-borne fungi. In contrast, root exudates containing PAP-H as well as additional chitinase, β-1,3-glucanase, and protease activities did inhibit the growth of soil-borne fungi. We found that PAP-H depurinates fungal ribosomes in vitro and in vivo, suggesting an additive mechanism that enables PAP-H to penetrate fungal cells.